Technical Design of Mine Sequence (Trimonth) in Coal Mining Based on Existing Mechanical Equipment at PT. Mega Bara Semesta Jobsite PT. SBP, Muara Enim Regency, South Sumatera - Muhammad Izhar Yusran; Edy Nursanto; Wawong Dwi Ratminah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to make a technical design for coal mining in the first quarter of 2022 which includes a mining progress design, disposal design. The research methodology includes literature study to find literature references that directly support and relate to mining technical design. Then conduct orientation and observation of the problems that exist in the field. The data needed in this study are primary data and secondary data. The data that has been obtained is then processed and analyzed to produce a conclusion in the form of a mining technical design that meets the coal production target of 135,000 tons/quarter. Mining progress plan is made based on a predetermined production target of 135,000 tons/ quarter of coal. The results of the reserve based on the design in January 2022 obtained overburden volume of 166,637 BCM, coal of 45,348 tons with SR = 3.67: 1, in February 2022 obtained overburden volume of 167,655 BCM, coal of 45.017 tons with SR = 3,72 : 1, in March 2022 obtained overburden volume of 166,541 BCM, coal of 45,127 tons with SR = 3.69 : 1. The disposal design is located 1,893.09 m south of the pit. The total disposal capacity based on the design is 552,763 CCM with an area of 9.72 Ha. The amount of disposal capacity is 2.5% higher per year against the reserve based on the design with the type of embankment applied is the Terrance Dump. The type of Terrace Dump embankment was chosen because the topography in the study area is not too steep.